Transcription factor ELF4 in physiology and diseases: Molecular roles and clinical implications - Dian Hu; Zerui Zhang; Yijun Wang; Siwen Li; Jiaqian Zhang; Zhangfan Wu; Mengyu Sun; Junqing Jiang; Danfei Liu; Xiaoyu Ji; Shuai Wang; Yufei Wang; et al. (Genes and Diseases)
Transcription factor E74 like ETS transcription factor 4 (ELF4), a member of the ETS family, is highly expressed in normal human hematopoietic tissue, ovary, placenta, colon, and certain pathological cell lines. During normal physiological processes, ELF4 regulates differentiation in osteogenic, adipocyte, and neuronal types. It also exerts a critical impact on the development of the immune system. However, its function is dysregulated through posttranslational modifications, gene fusions, and complex signaling crosstalk under pathological conditions. Furthermore, serving as a double-edged sword in cancer, ELF4 exhibits both tumor-suppressing and tumor-promoting effects. Specifically, ELF4 plays a critical role in cancer metastasis, proliferation, and modulation of the tumor microenvironment. This review provides an in-depth overview of the molecular structure and post-translational modifications of ELF4. It also summarizes the hallmarks of ELF4 in physiology and diseases, with a particular focus on its significance in oncology. Notably, this review underscores the potential of ELF4 as a prognostic biomarker, highlighting its clinical relevance. Finally, it discusses unresolved questions and future research directions of ELF4. An in-depth understanding of ELF4 biology could facilitate its clinical translation and offer promising targeted therapeutic strategies.